Premature Infant Swallowing: Patterns of Tongue-Soft Palate Coordination Based Upon Videofluoroscopy - Goldfield, Eugene C. (2010)
Coordination between movements of individual tongue points, and between soft palate elevation and tongue movements, were examined in 12 prematurely born infants referred from hospital NICUs for videofluoroscopic swallow study (VFSS) due to poor oral feeding and suspicion of aspiration. Detailed post-evaluation kinematic analysis was conducted by digitizing images of a lateral view of digitally superimposed points on the tongue and soft palate. The primary measure of coordination was continuous relative phase of the time series created by movements of points on the tongue and soft palate over successive frames. Three points on the tongue (anterior, medial, and posterior) were organized around a stable in-phase pattern, with a phase lag that implied an anterior to posterior direction of motion. Coordination between a tongue point and a point on the soft palate during lowering and elevation was close to anti-phase at initiation of the pharyngeal swallow. These findings suggest that anti-phase coordination between tongue and soft palate may reflect the process by which the tongue is timed to pump liquid by moving it into an enclosed space, compressing it, and allowing it to leave by a specific route through the pharynx.